(3GdEOGQI GdeGdjI (B:s (3GdeONd Gdcej (B/s - (3GdSGeQGFj, YOfGf gGTes ((3YeGf(B: s (3OGQ RgQGf(B, s)
(3GdGOGQI GdeGdjI (B: (3Gdeaghe , GdGgejI h GdhXGFa , GdGUhd GdeJOGhdI (B: (3eaghe h GOGQI , GdNUhe GdeJOGhdI (B: (3eaghe h GOGQI , GdJMdjd GdeGdj (B: (3eaghe h eDTQGJ , GdGOhGJ GdJMdjdjI , GdejRGfjGJ GdJbOjQjI (B: (3eaghe h GgejI , GdJfHD h GdGfhGY, GdbhGFe GdeGdjI GdJbOjQjI , GdJNWjW GdeGdj h gjcd GdJehjd , Jehjd GdeTQhY , GdJNWjW GdGSJKeGQj , GdGfaGb GdGSJKeGQj (B.s
(3eQGLY U(B.347 (3;GdedGMb h GdLOGhd U(B.353s
Keywords: (3GdGOGQI GdeGdjIs; (3GdESJKeGQs; (3GdJMdjd GdeGdjs; (3GdJNWjW GdeGdjs